1989
DOI: 10.1017/s0031182000058698
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cholinergic and serotoninergic drugs on motility in vitro of Haplometra cylindracea (Trematoda: Digenea)

Abstract: The spontaneous activity of the somatic muscle of the amphibian lung fluke, Haplometra cylindracea has been recorded in vitro, using an isometric force transducer system. Normal movement consisted of a continuous series of regular contractions which were maintained for over 4 h. Acetylcholine (ACh) inhibited motility at a concentration of 1 X 10(-3)M induced a flaccid paralysis. A similar response occurred with the cholinomimetric drugs, carbachol and nicotine, although in these instances the inhibition was le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The same inhibitory effect was observed when the worms or muscle strips were treated with classical cholinergic agonists or AChE inhibitors, whereas antagonists generally increased motor activity Sukhdeo et al 1984 ;Sukhdeo, Sangster & Mettrick, 1986 ;Thompson, Sangster & Mettrick, 1986 ;Maule et al 1989 ;McKay et al 1989). These observations led to the identification of ACh as an inhibitory neuromuscular transmitter of flatworms.…”
Section: Neuromuscular Effects Of Ach In Parasitic Flatwormsmentioning
confidence: 61%
“…The same inhibitory effect was observed when the worms or muscle strips were treated with classical cholinergic agonists or AChE inhibitors, whereas antagonists generally increased motor activity Sukhdeo et al 1984 ;Sukhdeo, Sangster & Mettrick, 1986 ;Thompson, Sangster & Mettrick, 1986 ;Maule et al 1989 ;McKay et al 1989). These observations led to the identification of ACh as an inhibitory neuromuscular transmitter of flatworms.…”
Section: Neuromuscular Effects Of Ach In Parasitic Flatwormsmentioning
confidence: 61%
“…There have been no reports of pharmacological studies on the effects of 5-HT on digenean cercariae, presumably because of the difficulties involved with working on such small preparations. Previous studies of adult digeneans have demonstrated a likely excitatory role for 5-HT on muscle (Beretta, 1969;Fretterer et al 1977;Holmes & Fairweather, 1984;Pax et al 1984;McKay et al, 1989) and it might be predicted that 5-HT has a similar excitatory role on cercarial muscle. If proven, 5-HT could be important in motility, host location and subsequent host penetration by S. inermis cercariae.…”
Section: Discussionmentioning
confidence: 93%
“…Immunocytochemical data also indicates the presence of 5‐HT in the nervous system of trematodes (Barton, Halton, Shaw, Maule, & Johnston, 1993; Fairweather, Maule, Mitchell, & Halton, 1987; Magee, Cahir, Halton, Johnston, & Shaw, 1993; McKay et al, 1991; Terenina et al, 2020; Tolstenkov et al, 2010). It is assumed that 5‐HT plays a role as an excitatory neurotransmitter in flatworms inducing muscle contraction (El‐Shehabi, Vermeire, Yoshino, & Ribeiro, 2009; McKay, Halton, Allen, & Fairweather, 1989; Moneypenny et al, 2001; Patocka, Sharma, Rashid, & Ribeiro, 2014; Pax, Siefker, & Bennett, 1984; Thompson & Mettrick, 1989; Zamanian et al, 2011).…”
Section: Discussionmentioning
confidence: 99%